The indigenous logistics system in Africa: The case of Nigeria, past to present - Adebayo Adeleke (Logistics, 2022)
Background: Centuries after its introduction in Africa, the western-style logistics system has not replicated the same results as it has in other parts of the world. The continent continues to grapple with poor logistics infrastructure and low intra-Africa trade at a time when governments in Africa are committed towards the expansion of trade and manufacturing through the implementation of the African Continental Free Trade Area (AfCFTA) agreement. There is a pressing need, therefore, for the development of a logistics system designed for the African socioeconomic environment and the peculiarities of the people. Methods: This paper examines the operations of the Indigenous Logistics Systems (ILS) in pre-colonial Nigeria and its development over time through qualitative data gathered from the six geopolitical zones in Nigeria and a review of literature. Results: ILS in Nigeria is the cultural creation of the people through the efficient management of available resources and the use of indigenous knowledge. The system derives its strengths and effectiveness from its availability, simplicity, affordability, and trust. Conclusions: The paper concludes that if improved with the application of simple technology, ILS has the answers to the challenges of logistics and Supply Chain Management (SCM) in Africa.
Keywords: 650; Africa; indigenous logistics system; logistics; supply chain; supply chain management